Examining the variables influencing religious leaders' interest in Bhagavad Gita studies: A case study of susut sub-district - Wiguna, I Kadek Jaya (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Bhagavad Gita is a sacred text in the Hindu tradition that contains teachings about duty (dharma), devotion (bhakti), wisdom (jnana), and discipline (yoga). This research aims to understand the factors that influence the interest of Pemangku (Hindu priests) in Susut District, Bangli Regency, Bali, in studying the Bhagavad Gita. Methods: Using qualitative research methods, data were obtained through a combination of open and closed questionnaires comprising 34 questions. Finding: The research results show that the majority of Pemangku have undergraduate education (30%) and junior high school education (30%), with 50% of them having never read the Bhagavad Gita. The primary motivations for those who study the Bhagavad Gita are self-development, spiritual improvement, and facing life challenges. Despite high interest, the Pemangku face obstacles such as limited access to learning resources (50%) and difficulty understanding the contents of the text without guidance. The discussion reveals the importance of a structured learning approach involving mentors or teachers and strengthening social support in the learning process. Additionally, adaptive and accessible learning methods need to be developed to bridge the gap between ancient texts and modern life contexts. Conclusion This research concludes that the interest of Pemangku in the Bhagavad Gita is influenced by educational background, personal motivation, learning methods, and access to learning resources. Recommendations are provided to improve the accessibility and quality of learning this sacred text in the future.